The comparative analysis of marketing activities among rural women entrepreneurs in Fars province, Iran - Kurosh Rezaei-Moghaddam; Ommolbani Karami; Mahsa Fatemi (Journal of Global Entrepreneurship Research, 2019)
Entrepreneurship has become the crucial subject of discussion among social and economic development specialists as the key to solving problems and reducing obstacles to human development. On the other hand, marketing is also considered as a main factor for entrepreneurial businesses' survival and progress. Thus, low marketing skills in small businesses often lead to lower performance levels and higher risk failures. The present study aimed to identify and analyze the marketing activities among rural women entrepreneurs. This research was conducted using a survey method among women entrepreneurs who were the members of agricultural development specialized holding companies in Fars province, Iran. A random sampling method was used to select 307 rural entrepreneurial women. According to the findings, marketing methods such as face-to-face advertising, making phone calls, participating in exhibitions, and sending text messages by women entrepreneurs are widely used. In applying the marketing methods, paying attention to the components of the marketing mix, and applying marketing strategy, women entrepreneurs in Marvdasht had the highest score. The entrepreneurial women in Marvdasht are more risk-takers, who use both marketing methods and strategies more often than women in other cities of Fars. Finally, some suggestions were presented to improve women entrepreneurs' marketing activities.
Keywords: 650; Marketing mix; Women entrepreneurs; Network marketing; Promotion; Competitive; Product satisfaction